Theory and Methods of Quantification Design on System-Level Electromagnetic Compatibility - Su, Donglin; Xie, Shuguo; Dai, Fei; Liu, Yan; Jia, Yunfeng (Springer Nature Singapore : Imprint: Springer, 2019)
This book systematically explains the fundamentals of system-level electromagnetic compatibility and introduces the basic concept of system-level electromagnetic compatibility quantification design. The topics covered include the critical technologies in the top-down quantification design of electromagnetic compatibility, quantification design of system-level electromagnetic compatibility, evaluation methods and application examples, quality control and application examples of electromagnetic compatibility development process, and real-world engineering example analysis of electromagnetic compatibility. The book proposes a top-down system-level electromagnetic compatibility quantification design method and is the first book to describe in detail how to quantitatively evaluate and predict system-level electromagnetic compatibility performance. It includes abundant engineering examples and experimental data demonstrating the usage and results of the top-down quantification design methods of system-level electromagnetic compatibility. It enables readers to obtain a thorough understanding of the theory and methods of system-level electromagnetic compatibility quantification design as well as the methodologies for engineering practice.